A dinâmica dos espeços públicos de lazer em cidades da aglomeração urbana de Londrina - PR - Bortolo, Carlos Alexandre de (2015)
This thesis seeks to analyze the different forms of use and appropriation different public spaces present in the cities of the urban agglomeration of Londrina - PR in contemporary experience through the most varied Socio-spatial relations experienced in daily life of each city. Our objectives were guided by an analysis of the production of public spaces in their singularities and the whole of the cities that make up this urban agglomeration, composed of Londrina, Jataizinho, Ibiporã, Cambé and Rolândia. These cities of different sizes, characteristics that ultimately produce areas with similarities and differences. The working hypothesis is that public spaces are produced and suitable in different times, by different people in different ways to its use and ownership, this being transformed by and from the social relations of production in cities of different sizes. The public spaces here studied represent sociability spaces conducive to numerous features. These over time have taken numerous meanings, different functions, representing other references to the cities in the process of production and the social transformations. Such processes could be seen and are linked the various actions and economic, political, social and cultural aspects of society in Brazil. Thus, our central argument of the thesis, then, is that we argue that public spaces remain key elements to urban constitution and life in cities. Discussing the vitality of public spaces today with its different uses and appropriations, as these areas are vital today and the urban agglomeration of Londrina.